Factors Related to the Incidence of Diabetes Mellitus in the Kebon Baru Primary Health Center in South Jakarta in 2020 - Ruth Tabitha; Syahrizal Syarif; Tri Yunis Miko Wahyono (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Diabetes Mellitus is a health problem encountered in Indonesia as well as in the world, it can be seen from the number of sufferers that continues to increase every year. Data from the International Diabetes Federation (IDF) shows that the number of people with Diabetes Mellitus in 2015 has reached as many as 415 million people and increased in 2017 to 425 million people worldwide. The Basic Health Research (Riskesdas) showed an increase in the prevalence of Diabetes Mellitus in Indonesia from 6.9% in 2013 to 8.5% in 2018. At the Kebon Baru Health Center, Diabetes Mellitus was among the top 10 diseases in 2019 with 529 cases. Various counseling programs to prevent non-communicable diseases are carried out, the priority program is by organizing the Chronic Disease Management Program (Pronalis) and by counseling. Objective: The aim of this study is to determine the factors associated with the incidence of Diabetes Mellitus at the Kebon Baru Community Health Center, South Jakarta, in 2020. Method: This study used a quantitative approach with cross sectional design by analyzing the secondary data of the monthly report of Non-Communicable Diseases at Kebon Baru Primary Health Center in 2020. These data were collected in 2020 and analyzed in 2021. Result: The prevalence of Diabetes Mellitus at Kebon Baru Primary Health Care in 2020 was 16.5% with the average blood sugar level of 153 mg/dL. The variables that were proven to have a relationship with the incidence of Diabetes Mellitus were the variable age with a p value of 0.001 (OR 3.15; 95% CI 1.56-6.36) and the variable history Diabetes Mellitus with a p value of 0.00 (OR 5.3; 95% CI 2.74-10.37). Conclusion: Patients who go to Kebon Baru Primary Health Care at the age ranging from 45 years and over have a 3.15 times risk of suffering from Diabetes Mellitus than those in the age group under 45 years. In addition, patients who go to the Kebon Baru Primary Health Center and have family members suffering from Diabetes Mellitus have a risk of 5.33 times to suffer from DM than those who do not.